1996
DOI: 10.1086/177210
|View full text |Cite
|
Sign up to set email alerts
|

Exact Solutions for Steady State, Spine, and Fan Magnetic Reconnection

Abstract: The problem of steady state, incompressible magnetic reconnection in three dimensions is addressed. It is shown that exact reconnection solutions can be constructed by superposing nonlinear disturbances onto three-dimensional magnetic X-points. There are two distinct families of reconnection solutions. These can be understood in terms of the eigenstructure of the null, that is, in terms of the " spine" curves and "fan" surfaces that define the separatrices of the field. One family of solutions is driven by dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 4 publications
4
90
0
Order By: Relevance
“…1 t lnjjDx 0f tx0 ðÞ jj; (22) where jj Á jj is defined as the Euclidean norm. Equation (22) provides us with only one LCE since we have only considered a single tangent vectorũ 0 .…”
Section: A Calculating the Complete Lyapunov Spectrummentioning
confidence: 99%
“…1 t lnjjDx 0f tx0 ðÞ jj; (22) where jj Á jj is defined as the Euclidean norm. Equation (22) provides us with only one LCE since we have only considered a single tangent vectorũ 0 .…”
Section: A Calculating the Complete Lyapunov Spectrummentioning
confidence: 99%
“…1,2002 CURRENT SHEET FORMATION IN CORONAL LOOPour model found. A more careful analysis of this approach will appeal to the dynamic response of a magnetic null point, a topic of ongoing investigation (Hassam 1992;Craig & Fabling 1996). In order to specify a field-line mapping, we assumed the chromosphere to be in force-free equilibrium.…”
Section: The Boundary Conditionmentioning
confidence: 99%
“…At this point there is still significant current in the system which slowly reduces through magnetic diffusion. Such fan plane perturbations are reminiscent of the radially symmetric non-reconnecting m = 0 spine mode of Craig & Fabling (1996) hinting that such solutions could be utilized to analyze such oscillations in the future. For much longer time frames this oscillatory motion will damp out (which we see begins to occur around t = 10 in Fig.…”
Section: Temporal Variation: Relaxation Phasementioning
confidence: 99%
“…Subsequently it has been shown that twisting motions about the spine/fan create a current sheet along the fan/spine leading to Torsional fan/spine respectively (Priest & Pontin 2009). Shearing motions of the spine or fan in the incompressible situation give rise to current accumulation at the fan and spine respectively (Priest & Titov 1996;Craig & Fabling 1996) known as fan and spine reconnection. When finite plasma compressibility is invoked the plasma pressure gradient is too weak within the planar current sheets of both cases to resist the Lorentz force driven spine-fan collapse and a current sheet forms at an angle to the spine and fan within which "spine-fan" reconnection takes place (Priest & Pontin 2009;Pontin et al 2007a,b).…”
Section: Introductionmentioning
confidence: 99%